PENGARUH MOTIVASI, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI SEKRETARIAT DPRD DI KABUPATEN LEBAK - Juliansyah Noor; Mulyono Mulyono (Universitas La Tansa Mashiro, 2020)
This study aims to obtain information related to the possibility of whether job performance is influenced by motivation and job satisfaction. Using the causal study through a survey at the Secretariat of the Lebak Regency DPRD, Indonesia, for a sample of 69 employees, data for each variable was collected separately by respondents who filled out the questionnaire. Pathway techniques are applied to analyze data previously treated with regressive correlations and procedures. The results prove that employee performance is directly affected by work motivation and job satisfaction. The findings show that variations in job performance have been influenced by work motivation and job satisfaction in organizations. This further implies the need to consider the variables of job performance, work motivation, and job satisfaction in the strategic planning of human resource development in the Lebak Regency DPRD Secretariat under studied.